A new optimization approach for high efficiency of FTO/InS/CIS heterojunction solar cells. (4th July 2022) - Dabbabi, Samar; Seboui, Z.; Tlili, M.; Jebbari, N.; Garcia-Loureiro, A.; Kamoun, Najoua
ABSTRACT: In this work, a new approach is developed to optimize FTO/InS/CIS hetero-junction solar cell using the Slivaco-Atlas software. Each single thin film was prepared by spray pyrolysis method on glass substrates in order to characterize its proper material parameters. Structural and morphological analysis confirmed the deposition of F-doped SnO2, In2 S3 and CuInS2 films with porous structures. The extracted physical properties such as thickness, optical, and electrical parameters are considered as input data for Silvaco-Atlas software simulation. It was found that thickness layers and carrier concentration of CIS-based solar cell play an important role in determining solar cell performances. The combination of the optimum parameters enables to obtain the efficiency of 38.20%. The overall investigation on CIS solar cell gives potential suggestions that may lead to the fabrication of the high-efficiency CIS-based solar cell.